(untitled) (Research, Society and Development, 2020)
Adolescent pregnancy is a public health problem. This research aimed to understand the care process of nurses in the face of adolescent pregnancy in Primary Care and to identify the main difficulties faced when dealing with this group. This is an exploratory and descriptive research of a qualitative nature with 10 nurses registered in the Family Health Strategy teams in municipalities in the State of Piauí, Brazil. A semi-structured interview script and in-depth analysis of the collective subject’s discourse was used. Through the data obtained, it was noticed that most of the volunteers were female, in the age group of 18 to 40 years old with working time of 1 to 5 years. It was possible to analyze the nurses’ knowledge about the care provided to pregnant adolescents, and it was noticed that most of the nurses interviewed demonstrated insufficient and ineffective knowledge in their work with pregnant adolescents. In general, nurses do not have a differentiated and specific approach for this group, which generates numerous barriers to obtain quality care, such as non-adherence to prenatal care, difficulty in forming trusting relationships, lack of support of families and little commitment and interest in prenatal care, childbirth and the puerperium.